The Importance of the System Category in Security Studies - Gierszewski, Janusz (Historia i Polityka, 2023)
Using qualitative methods of source analysis and tracing the process of scientific discourse, an attempt was made to answer the research question: What is the relevance of the system category for security sciences? The study provides arguments in favour of confirming the author’s hypothesis that the category of system constitutes one of the universes of security sciences in terms of research object as well as methodology. In addition, the category is important for defining the identity of this scientific discipline.